2015
DOI: 10.1108/jcm-11-2014-1220
|View full text |Cite
|
Sign up to set email alerts
|

Promoting biodiversity: do consumers prefer feelings, facts, advice or appeals?

Abstract: Purpose – The purpose of this paper is to explore consumers’ responses to emotional and normative communication in comparison with traditional informational campaigns promoting pro-environmental behavior in the context of biodiversity. By adopting the approach of likeability of the communication, the paper identifies which type of communication strategy is liked by consumers’ and which dimensions define likeability in the context of biodiversity. The goal is to improve the effectiveness of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Conservation marketing techniques evaluated in this body of research included written text or messages (Hart & Larson ; Schaffner et al. ), still images (Ross et al. ), videos (Weinstein et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservation marketing techniques evaluated in this body of research included written text or messages (Hart & Larson ; Schaffner et al. ), still images (Ross et al. ), videos (Weinstein et al.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies found statistically significant differences in outcome scores depending on which video was viewed; however, it was not possible to calculate effect sizes due to the provision of insufficient detail except for 1 outcome in Pearson et al (2011) in which students reported increases in target behaviors from 23% to 85% (OR of 1.35 or small effect). It was not possible to conduct further synthesis of findings from the 14 studies that evaluated conservation-marketing techniques because of the poor methodological quality of these studies (e.g., 3 did not include a comparator group [Dikou & Dionysopoulou 2011;Shaw et al 2014;Schaffner et al 2015]).…”
Section: Narrative Synthesis Of Findingsmentioning
confidence: 99%
“…Relating to current studies on pro‐environmental behaviours, Schaffner et al . () have found that attention is on negative emotions of the individual, yet both positive and negative emotions influence individuals’ intention to act pro‐environmentally. Emphasizing the preceding proposition, Bamberg () and Schaffner et al .…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In this paper, positive or negative emotion refers to the positive or negative mental states when household electricity conservation behaviours are being performed (Wang et al, 2018). Studies have shown that both positive and negative emotional factors such as: pride, excitement, happiness, satisfaction, guilt, anger, contempt, shame and sadness can determine pro-environmental and conservation behaviours (Jhangiani et al, 2015;Schaffner et al, 2015Schaffner et al, , 2017Han and Hyun, 2018). Relating to current studies on proenvironmental behaviours, Schaffner et al (2015) have found that attention is on negative emotions of the individual, yet both positive and negative emotions influence individuals' intention to act pro-environmentally.…”
Section: Emotionsmentioning
confidence: 99%
See 1 more Smart Citation